Influence of Behavioral Aspects on Stock Investment Decision-Making - Pant, Dinesh; Pant, Sneha (The Management Review, 2025)
Investment decision making is a complex process influenced by psychological biases, especially in emerging markets such as Nepal, where financial literacy and market transparency remain limited. Traditional finance models assume rational investor behavior, but behavioral finance highlights the significant role of cognitive biases, such as loss aversion, overconfidence, herding, and risk perception, in shaping investment choices. This study examines the impact of these behavioral factors on individual investors in the Nepalese stock market. This study adopted a quantitative approach using a structured questionnaire distributed to 387 respondents. Descriptive statistics and multiple regression analysis were employed to explore the relationship between the independent variables (loss aversion, overconfidence, herding, and risk perception) and dependent variable (investment decision). The results reveal that loss aversion (B = -1.416, p < 0.01) and risk perception (B = -1.362, p < 0.01) negatively impact investment decisions, while overconfidence (B = 0.947, p < 0.01) and herding (B = 1.723, p < 0.01) have positive effects. Among these, herding has the strongest influence, indicating that social dynamics play a crucial role in investment behavior. These findings emphasize the need for targeted financial literacy programs to address cognitive biases and promote rational decision-making. Enhancing market transparency and access to reliable information can reduce emotional decision-making and improve market stability. This study contributes to behavioral finance literature by offering localized insights into investor behavior in an emerging market context.